Upaya Pengentasan Kemiskinan Oleh Pemerintah Desa di Desa Traji Kecamatan Parakan Temanggung - Ratna Sari Wijayanti; Isnaini Muallidin (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
The problem of poverty almost occurs in almost all areas including Traji Village. To alleviate poverty requires proper methods with careful calculations by the village government. The aim is to find out how the efforts of poverty alleviation by the village government in the Traji cultural village, Parakan District, Temanggung. The method used in this research is descriptive qualitative which is a research that conducted based on a qualitative paradigm, strategy, and model implementation. The final result of this research is that in the effort to alleviate poverty in the cultural village of Traji, Parakan Subdistrict, Temanggung Regency, there are several problems, such as less than optimal services due to the limited facilities and infrastructure owned by the village, lack of training for village apparatus, and program achievements that are too minimal. thus making poverty alleviation difficult to achieve. However, the village government continues to carry out its duties by seeking various ways to alleviate poverty, such as holding Peken Lepen which can generate 6 million per performance and has a good impact on the village economy. Peken Lepen is a commitment from the village government to the economy of the local community. In addition, the government also involves all communities and government institutions such as the Activity Management Team Village Consultative Body and stakeholders by holding hamlet meetings, which is proof that the government is not the sole authority.